Fabrication of a modified straw cellulose and cerium oxide nanocomposite and its visible-light photocatalytic reduction activity. Issue 4 (August 2017) - Zhang, Ya; Zhou, Zhifeng; Yuan, Kechun; Wen, Fangfang; Tan, Jing; Hu, Chun; Wang, Honggui
Highlights: Straw cellulose (SC) decorated CeO2 nanocomposite was prepared via a hydrothermal method. TEM images display carbon nanotube-like SC has grown on the surface of CeO2 . The SC-CeO2 nanocomposite has good visible light photocatalytic activity on reduction of aqueous Cr(VI). Abstract: A straw cellulose-cerium oxide (SC-CeO2 ) nanocompsite has been synthesized through a hydrothermal method. Before this, the SC is oxidized and functionalized by a 2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical (TEMPO)-mediated oxidation. The as-obtained SC displays carbon nanotube-like nanocellulose. When composited with CeO2, the nanocellulose grows on the surface of CeO2 . The synergistic effect between SC and CeO2 results in an efficient separation of photogenerated carriers in the SC and CeO2 coupling system. It is confirmed in this work that the SC-CeO2 nanocomposite has good visible light-induced photocatalytic activity on reduction of aqueous Cr(VI) under acid condition (pH 4–6). More than 95% Cr(VI) (3–5 ppm) can be reduced under visible light irradiation for 60 min. Photocatalyst dosage and Cr(VI) concentration affect the conversion rate greatly.